The degree of the application of knowledge management processes in "Al-Saeed University" and their impact on the excellence of institutional performance - Noman, Mohammed Saif Mohamed (Journal of Economic, Administrative and Legal Sciences, 2023)
This study aimed to identify the reality of the application of Knowledge management at Al-Saeed university. The study included all the current employees of the university and the faculty of teaching which numbered" 76 “and to achieve the conclusion of the study objectives, the researcher prepared a questionnaire that included "71" paragraphs distributed over three axes. He used the descriptive analytical approach and the method of a comprehensive survey of all the aspects of the study. The study concluded that the degree of the application of knowledge management processes was "strong" with an arithmetic average of”3,58” and a relative weight of”71.6%” and a standard deviation of “ 0.621 “furthermore the degree of the application of excellence of institutional performance was "strong" with an arithmetic average of”3.40” and a relative weight of”68%” and a standard deviation of “0.746” The study concluded that there is a strong and positive relationship between the application of knowledge management processes and the impact of institutional excellence, the study also showed the presence of statistically significant differences at the level of( 0,05) attributed to the age, years of experience, job title, and qualification The conclusion of the study shows the construction of a strategic Vision of Knowledge administration and The variety of its activities as well as providing all aspects and declaring all obstacles and difficulties Facing the issue.